Preparation of a PES/PFSA-g-MWCNT ultrafiltration membrane with improved permeation and antifouling properties. (1st March 2021) - Wang, Chengcong; Zhang, Lijuan; Yuan, Haikuan; Fu, Yujia; Zeng, Zheng; Lu, Jie
Abstract : In this study, perfluorosulfonic acid (PFSA) was firstly grafted on multi-walled carbon nanotubes (MWCNTs) to obtain PFSA- g -MWCNT nanocomposites. Abstract : In this study, perfluorosulfonic acid (PFSA) was firstly grafted on multi-walled carbon nanotubes (MWCNTs) to obtain PFSA- g -MWCNT nanocomposites. The combination of MWCNTs with PFSA effectively prevents the interactions among them, so that the dispersion of PFSA- g -MWCNTs in N, N -dimethylacetamide (DMAc) was greatly improved. Then, polyethersulfone (PES)/PFSA- g -MWCNT ultrafiltration (UF) membranes were prepared via a non-solvent induced phase separation (NIPS) method using different contents of PFSA- g -MWCNT nanocomposites as additives. The nanocomposites and membranes were characterized using techniques including Fourier-transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy (SEM). The SEM images show that the PFSA- g -MWCNTs no longer agglomerate and entangle, and exist as individual nanotubes in the PES/PFSA- g -MWCNT membrane. The mechanical and thermal properties of the composite membranes were enhanced with the increasing PFSA- g -MWCNT nanocomposite content. The performance of the UF membrane was evaluated using bovine serum albumin (BSA) as a model system. The results show that the permeation and antifouling performances of the PES/PFSA- g -MWCNT membranes were enhanced. For example, the pure water flux, BSA rejection and pure water flux recovery rate of the PES (M0) membrane were 80.49 L m −2 h −1, 86.29%, and 70.96%, respectively, while for the PES/PFSA- g -MWCNT (M6) membrane, they were 447.83 L m −2 h −1, 87.47%, and 92.10%, respectively. Long-term stability experiments show that the PES/PFSA- g -MWCNT membrane still maintains a high pure water flux.